Kerajaan Allah sebagai Landasan Teologi Moderasi Beragama di Indonesia - Silitonga, Ewen Josua; Saragih, Janhotner (CV. Creative Tugu Pena, 2024)
Indonesia is a nation that is multi in terms of culture, religion and very pluralistic because Indonesia is an archipelago, on the one hand diversity is the wealth of the nation but on the other hand diversity has the potential to become disentegration, intolerance and radicalism that damage the unity of the nation's children and inter-religious life. The fact of diversity that is misinterpreted will lead to the phenomenon of religious devaluation, and in Indonesia religious devaluation is the main indicator not of secularisation but of religious politicisation. This destructive situation should not be left unchecked and must be addressed by every religion theologically, especially Christianity, which is to spawn, hatch an attitude of religious moderation in Indonesian society. By the paradigm of moderation, the competition of religions is not a matter of doctrinal differences but a competition of what religions contribute to the values of life and humanity. The author sees that the teachings of the Kingdom of God need to be reconstructed as the foundation of religious moderation, because today the values of the teachings of the Kingdom of God have been narrowed only for private interests even though the true values of the Kingdom of God are public and universal. Keywords: Kingdom of God, Religious Moderation, Christianity